Freewater - Luqman-Dawson, Amina (New York : Little, Brown and Company, 2022)
After fleeing the plantation where they were enslaved, siblings Ada and Homer discover the secret community of Freewater, and work with freeborn Sanzi to protect their new home from the encroaching dangers of the outside world.
Prologue -- The journey -- Freewater -- The return -- A note from Amina.
5-8
4.6
OBOB MS 2024-2025.
Keywords: African Americans -- Juvenile fiction; Slavery -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Communities -- Juvenile fiction; African Americans -- Fiction; Slavery -- Fiction; Brothers and sisters -- Fiction; Communities -- Fiction; Historical fiction